ANALISIS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT PASANGKAYU DALAM MENDUKUNG INDONESIA KREATIF - Muh Faldi; Nining Vitria; Norce Christanti Ta'ela; Novitasari Novitasari; Nur Fadilla; Rian Rachdiat Maka; Candra Abubakar; Mastang Mastang; Fikra Fikra; Putri Chicianti Datu Adam; Rahmawati Halim; Askar Mayusa; Andi Maman (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study examines the implementation of Corporate Social Responsibility (CSR) programs by PT Pasangkayu in supporting the development of the creative economy in West Sulawesi. The research background is rooted in Indonesia’s national vision, Asta Cita, which positions the creative economy as a pillar of inclusive and sustainable development. The objective of this study is to analyze the contribution of Astra Kreatif programs to local community empowerment, particularly in enhancing economic independence and strengthening social solidarity. A qualitative descriptive approach was employed, using Focus Group Discussions (FGD) with company employees to explore perceptions, experiences, challenges, and socio-economic impacts of the CSR initiatives. The findings reveal that Astra Kreatif successfully strengthened the capacity of palm oil farmer groups, created diversified non-palm businesses (catfish farming, chili cultivation, poultry, and mushroom production), and fostered the growth of local MSMEs. These initiatives directly benefited 475 households across four target villages, generating new employment opportunities, increasing household income, and empowering women and youth in village-based economies. The implications highlight that creativity-driven CSR is not merely a corporate obligation but also a catalyst for inclusive and sustainable rural economic development, aligning with the broader vision of Indonesia Kreatif.